NAVIGATING GREY ZONES: INTEGRITY VULNERABILITIES IN REGIONAL GOVERNANCE - Rifqi Novriyandana; Iwan Alfanie; Sunardi; Reja Fahlevi; Dewi Sri Susanti; Arif Rahman Hakim; Muhammad Baqir; Muhamad Rafli (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
Formal integrity systems often fail to produce ethical outcomes in decentralized bureaucracies, giving rise to what this study conceptualizes as an "integrity paradox." This research investigates the structural and cultural vulnerabilities within Indonesian local governments that contribute to internal control failures. Using a qualitative case study approach, the study analyzes data from the Integrity Assessment Survey (SPI) and conducted in-depth interviews with internal and external stakeholders in South Kalimantan. The findings indicate that although formal anti-corruption instruments are technically in place, they are systematically undermined by "grey zone" practices, including normalized informal interventions and a pervasive culture of silence driven by fear of retaliation. The study further demonstrates that internal oversight functions, such as the Inspectorate, tend to be reactive rather than proactive. These findings suggest that strengthening public sector integrity requires moving beyond administrative compliance toward the institutionalization of whistleblower protection mechanism and audit-based early warning systems.